Exit plan of financial investors in growing businesses from legal and accounting aspects in Hungary - Sisa, Krisztina Andrea; Siklósi, Ágnes; Bárczi, Judit (Public Finance Quarterly, 2025)
Starting from the doctrinal distinction between the company contract and the syndicate contract, the paper presents, through practical examples, the possibilities of enforcing complex ownership interests derived from the complementary institutional systems of company and contract law. In the case of joint stock companies, company law itself defines a multifaceted set of instruments for the practical regulation of the long-term owner-shareholder cooperation of founders (types of shares, classes of shares), which makes the joint stock company form the most suitable form of company for capital investment in the SME sector (especially for start-up companies). However, beyond the institutional framework of company law, practice has also developed a number of forms of contractual law to effectively model syndicated management (call and put options, drag-along and tag-along rights, etc.), with a focus on the detailed rules of the investment exit event regime. In addition to the legal guarantees to be provided to financial investors, the assets, financial and income situation of the investee company must be measured on an ongoing basis, based on a set of indicators that can be agreed in advance by the parties, in order to determine the optimal exit date. Accounting reports provide the primary information base for this metric system and therefore reliable and fair accounting reports are a key element in this decision and evaluation situation.